ICT-Aided Supervision and Teachers’ Job Performance in Secondary Schools in Calabar Education Zone of Cross River State, Nigeria. (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study aimed at determining the relationship between ICT-aided Supervision and Teachers job Performance in Secondary Schools in Calabar Education Zone, Cross River State, Nigeria. Two sub-variables were used to state the purpose of the study, research questions and statement of hypotheses. The population of the study consist of two thousand, nine hundred and thirty three teachers (2,933) in eighty-nine (89) public secondary schools in Cross River State. Stratified sampling technique was used in this study. A sample size of seven hundred and three (703) teachers were selected and used for the study. Instrument titled; Information and Communication (ICT)- aided Supervision andTeachers Job Performance Questionnaire (ICTASTJPQ) was used for data collection. The instrument was validated by two experts in test and measurement. A reliability estimates of 0. 78 and 0.86 was obtained using Cronbach alpha reliability estimate. Simple linear Regression was used for data analysis. The results of these findings revealed that there is a significant prediction of Closed-Circuit Television, Internet Facilities, Video- Conferencing and use of computers with teachers Job Performance. There was also a significant joint prediction of ICT-aided supervision with teachers Job Performance. Summary and implication to this study were made based on the result obtained from thisstudy. It was recommended therefore that school principals should ensure the use of CCTV primarily for safety, classroom management and enhancing teaching practices and not for micromanaging teachers. When used thoughtfully, CCTV can contribute to enhanced teacher’s performance, better classroom management and improved overall outcomes.
Keywords: ICT- based Supervision; teachers job performance; Classroom management instructional supervision